2009
DOI: 10.1177/1069397109335729
|View full text |Cite
|
Sign up to set email alerts
|

Personality, Health, and Coping

Abstract: This study explored group and relational differences in personality, health, and coping across 189 Australian students and 243 Singaporean students. Life Orientation Test—Revised showed a one-factor structure for Australians but a two-factor structure for Singaporeans. Australians tended to be more agreeable, more conscientious, more optimistic, more satisfied with their lives, while Singaporeans tended to be more neurotic and more pessimistic. Singaporeans tended to utilize less frequent adaptive and maladapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Neuroticism appears to reflect a negative cognitive bias that is positively associated with poor psychological outcomes and negatively related to psychological wellbeing. The results of the present study confirm previous findings on the positive association between neuroticism and distress (Aarstad et al, 2012;Beisland et al, 2013;Chien et al, 2007;Matthews et al, 2006;Wong et al, 2009) and the inverse association between neuroticism WINTER 2017 PSI CHI JOURNAL OF PSYCHOLOGICAL RESEARCH and wellbeing (Beisland et al, 2013;Gale, Booth, Mottus, Kuh, & Deary, 2013;Gutiérrez et al, 2005;James et al, 2012).…”
Section: Neuroticism and Psychological Outcomessupporting
confidence: 90%
See 2 more Smart Citations
“…Neuroticism appears to reflect a negative cognitive bias that is positively associated with poor psychological outcomes and negatively related to psychological wellbeing. The results of the present study confirm previous findings on the positive association between neuroticism and distress (Aarstad et al, 2012;Beisland et al, 2013;Chien et al, 2007;Matthews et al, 2006;Wong et al, 2009) and the inverse association between neuroticism WINTER 2017 PSI CHI JOURNAL OF PSYCHOLOGICAL RESEARCH and wellbeing (Beisland et al, 2013;Gale, Booth, Mottus, Kuh, & Deary, 2013;Gutiérrez et al, 2005;James et al, 2012).…”
Section: Neuroticism and Psychological Outcomessupporting
confidence: 90%
“…Not surprisingly, among the FFM personality traits, high neuroticism was the sole positive predic tor of anxiety and stress among both Australian and Singaporean undergraduates in one study (Wong et al, 2009). Matthews et al (2006) also found that neuroticism positively predicted stress and worry in undergraduates.…”
Section: Social Justice Education As a Responsibilitymentioning
confidence: 90%
See 1 more Smart Citation
“…According to prior work, East Asians score higher in neuroticism than European Americans (e.g., Wong, Lee, Ang, Oei, & Ng, 2009). Further, the experience of emotional lability (i.e., neuroticism) is correlated with emotional complexity, that is, the experience of positive and negative emotions simultaneously (Goetz, Spencer-Rodgers, & Peng, 2008).…”
Section: Methodsmentioning
confidence: 98%